Disentangling hindgut metabolism in the American cockroach through single-cell genomics and metatranscriptomics - Dukes, Helen E.; Tinker, Kara A.; Ottesen, Elizabeth A. (Frontiers in Microbiology, 2023)
Omnivorous cockroaches host a complex hindgut microbiota comprised of insect-specific lineages related to those found in mammalian omnivores. Many of these organisms have few cultured representatives, thereby limiting our ability to infer the functional capabilities of these microbes. Here we present a unique reference set of 96 high-quality single cell-amplified genomes (SAGs) from bacterial and archaeal cockroach gut symbionts. We additionally generated cockroach hindgut metagenomic and metatranscriptomic sequence libraries and mapped them to our SAGs. By combining these datasets, we are able to perform an in-depth phylogenetic and functional analysis to evaluate the abundance and activities of the taxa in vivo. Recovered lineages include key genera within Bacteroidota, including polysaccharide-degrading taxa from the genera Bacteroides, Dysgonomonas, and Parabacteroides, as well as a group of unclassified insect-associated Bacteroidales. We also recovered a phylogenetically diverse set of Firmicutes exhibiting a wide range of metabolic capabilities, including—but not limited to—polysaccharide and polypeptide degradation. Other functional groups exhibiting high relative activity in the metatranscriptomic dataset include multiple putative sulfate reducers belonging to families in the Desulfobacterota phylum and two groups of methanogenic archaea. Together, this work provides a valuable reference set with new insights into the functional specializations of insect gut symbionts and frames future studies of cockroach hindgut metabolism.